The Silent Garden : A Parent's Guide to Raising a Deaf Child - Ogden, Paul W. (Book collections on Project MUSE., 2016)
"Offers parents of deaf children the support and unbiased information needed to fully realize their children's potential. The completely revised third edition is a must-have resource for parents of deaf children"--